Managing the risk of fraud and misconduct [ meeting the challenges of a global, regulated and digital environment - Girgenti, Richard H.; Hedley, Timothy P. (New York : McGraw-Hill, 2011)
A high-level, strategy-based guide to protecting anyorganization from wrongdoers within
1. Understanding fraud -- 2. Understanding other forms of misconduct -- 3. A framework for an effective compliance program and illegal activity -- 4. A model for managing fraud
and misconduct prevention, detection, and response
Includes bibliographical references and index
Keywords: Accounting fraud; Computer crimes -- Investigation; Corporations -- Corrupt practices; Fraud -- Prevention